Prosocial thinkers and the social transmission of justice†. (19th May 2017) - Shteynberg, Garriy; Gelfand, Michele; Imai, Lynn; Mayer, David M.; Bell, Chris
Abstract: Feeling the sting of another's injustice is a common human experience. We adopt a motivated information processing approach and explore how individual differences in social motives (e.g., high vs. low collectivism) and epistemic motives (e.g., high vs. low need for closure) drive individuals' evaluative and behavioral reactions to the just and unjust treatment of others. In two studies, one in the laboratory ( N  = 78) and one in the field ( N  = 163), we find that the justice treatment of others has a more profound influence on the attitudes and behaviors of prosocial thinkers, people who are chronically higher (vs. lower) in collectivism and lower (vs. higher) in the need for closure. In all, our results suggest that chronically higher collectivism and a lower need for closure work in concert to make another's justice relevant to personal judgment and behavior.